2018
DOI: 10.14710/jksa.21.2.102-106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid on Natural Zeolite Dealumination on Indigo Carmine Adsorption Capability

Abstract: A r t i c l e I n f o A b s t r a c t Keywords: zeolite; dealumination; H2SO4; HCl; adsorption; indigo carmine Modifying natural zeolite with dealumination using H2SO4 and HCl, and its application to adsorb indigo carmine has been performed. Dealumination was carried out by reacting a natural zeolite with a mixture of KMnO4-H2SO4 and a mixture of KMnO4-HCl then refluxed for 5 hours followed by washing with demineralized water until a neutral pH was obtained and dried for 12 hours at 80°C. Dealuminated zeolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Zeolite damage caused by high concentrations of H2SO4 used in the activation process (Lestari, 2010). Termination of aluminum in the zeolite framework causes decrystallization which results in an increase of the amorphous phase of the zeolite (Sulistyowati et al, 2018). The results of XRD analysis added in figure 1 shows that some peaks at diffraction 2ϴ = 11.2 o , 13.4 o , 19.4 o , 19.6 o , 19.9 o , 21.9 o , 22.8 o , 23 o , 25.6 o , 26 , 3 o , 27.5 o had a higher intensity in the ZAB-1M sample compared to the ZAB-NA sample.…”
Section: Results and Discussion Zeolite Characterizationmentioning
confidence: 99%
“…Zeolite damage caused by high concentrations of H2SO4 used in the activation process (Lestari, 2010). Termination of aluminum in the zeolite framework causes decrystallization which results in an increase of the amorphous phase of the zeolite (Sulistyowati et al, 2018). The results of XRD analysis added in figure 1 shows that some peaks at diffraction 2ϴ = 11.2 o , 13.4 o , 19.4 o , 19.6 o , 19.9 o , 21.9 o , 22.8 o , 23 o , 25.6 o , 26 , 3 o , 27.5 o had a higher intensity in the ZAB-1M sample compared to the ZAB-NA sample.…”
Section: Results and Discussion Zeolite Characterizationmentioning
confidence: 99%
“…Zeolite is one of the materials capable of adsorbing Pb. This is because zeolites contain a hydrate crystallinaluminosilicate compound with high cation exchange properties capable of exchanging ions [9]. Zeolite has been widely used in the waste treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite is used as an adsorber because of its regular amorphous structure with interconnected cavities in all directions, the ability to absorb small molecules, and a very large surface area. , Moreover, the ability of zeolites to exchange catalysts via cation adsorption is what makes them beneficial to be used as adsorber materials. , In addition, zeolite is also known as a porous material and has several practical uses, such as filters and absorbents of moisture. The effect of zeolite adsorption is affected by the number and size of open pores on the zeolite surface . As a result, the activation process has a significant impact in determining the effectiveness of the zeolite capacity. , …”
Section: Introductionmentioning
confidence: 99%
“…19 As a result, the activation process has a significant impact in determining the effectiveness of the zeolite capacity. 20,21 Pahae-activated natural zeolite can absorb up to 53.82% of its weight in water. A previous study found that Pahae natural zeolite with a mesh size of 200 had a higher water vapor adsorption capacity than Cikalong natural zeolite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation